2023
DOI: 10.3390/molecules28124847
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Methods to Evaluate the Antioxidant Capacity of Propolis: An Attempt to Explain the Differences

Abstract: Propolis is a natural product produced by bees that contains a complex mixture of compounds, including phenolic compounds and flavonoids. These compounds contribute to its biological activities, such as antioxidant capacity. This study analysed the pollen profile, total phenolic content (TPC), antioxidant properties, and phenolic compound profile of four propolis samples from Portugal. The total phenolic compounds in the samples were determined by six different techniques: four different Folin–Ciocalteu (F-C) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 98 publications
0
3
0
Order By: Relevance
“…It has been shown that the high content of some flavonoids, such as quercetin, kaempferol, and galangin, affects the high antioxidant activity of propolis extracts [ 31 , 32 ]. The antioxidant capacity of flavonoids is mainly related to their chemical structure and, as with phenolic acids, is based on the O-H bond dissociation energy value [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the high content of some flavonoids, such as quercetin, kaempferol, and galangin, affects the high antioxidant activity of propolis extracts [ 31 , 32 ]. The antioxidant capacity of flavonoids is mainly related to their chemical structure and, as with phenolic acids, is based on the O-H bond dissociation energy value [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors conclude that the FRAP method has limitations and needs to be modified. The fact that it is based on an aqueous solution (acetate buffer) limits the method to hydrophilic substances, while some components of propolis with antioxidant properties (e.g., terpenes) are hydrophobic [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…After analyzing the quality parameters of G19-G22 unprocessed samples and assessing the chemical characteristics of the respective ethanol extracts, we shifted our focus to propolis' biological features, namely its antimicrobial and antioxidant capacities. According to Sheng et al [47], a natural product can be classified as a possible natural antioxidant if it exhibits DPPH• and ABTS• radical scavenging capacities, and previous studies reported Portuguese propolis on numerous occasions as a natural product with a high antioxidant capacity [18,25,48]. Falcão et al [21] described that ethanol extracts of propolis samples collected from Portuguese northern and coastal regions displayed EC 50 values ranging from 10 to 30 µg/mL, values notably and significantly lower compared to those reported for samples from other areas of Portugal.…”
Section: Discussionmentioning
confidence: 99%